Short Hagiographical Narrative Texts in Keršansko Devištvo by Anton Martin Slomšek (Preučevanje otroške in mladinske književnosti, 2025)
The paper examines short hagiographical narrative texts found in the devotional publication Keršansko devištvo: Potrebni nauki ino izgledi za žensko mladost (1834), by Anton Martin Slomšek in collaboration with young seminarians at Klagenfurt. Biographical examples portray female saints, presented with virtuous behavioral demeanor as worthy role models for young girls. In portrayal of their life realities, which exhibit modest fictional elements subordinate to a didactic imperative with extraliterary moral and religious educational functions, a distinctive combination of hagiographic genre characteristics with Enlightenment-philanthropic narrative patterns and their subsequent secularized Biedermeier versions, has been identified. These were assimilated through the translations of children's and youth literature originating from the German-Austrian linguistic sphere, indicating mutual syncretic connections.